Ethnochemistry Study of The Use of Plants as Traditional Medicine In The Community of Samadua District, South Aceh Regency - Abdul Gani; Erlidawati Erlidawati; Nurmalasari Nurmalasari (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2022)
Research on the ethnochemistry study of using plants as traditional medicine in the Samadua District community has been conducted. In general, there are two ways to use plants as medicine: internal medicine (oral) and external medicine (topical). This type of research is descriptive qualitative with an ethnographic approach that aims to determine the types, benefits, processing methods, and chemical content of plants used as internal medicine by the people of Samadua District. Data collection techniques in this study were observation, interviews, and documentation. The sampling technique was carried out by purposive sampling, namely by conducting interviews with herbal practitioners, community leaders, and users. The results showed that in Samadua District, 54 plants were used by the community to treat diabetes, high blood pressure, cough, gout, cholesterol, diarrhea, and other complaints. Medicinal plants are processed by boiling, grinding, kneading, eating, making juice, or brewing. The most processing method is boiling at 46.34%, while the least is brewing at 1.21%. Plants can be used as drugs because they contain certain chemicals produced from secondary metabolites. The chemical constituents of these medicinal plants include flavonoids, alkaloids, saponins, tannins, terpenoids, phenolic compounds, glycosides, vitamins, steroids, and essential oils. Ethnochemistry studies combine public opinion with science regarding the effectiveness of plants considered useful as drugs based on the chemical compounds contained in these plants.